2021
DOI: 10.1186/s40902-021-00302-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of autogenous tooth bone graft material without organic matter and type I collagen treatment on bone regeneration

Abstract: Objectives The aim of this study is to examine the effect of particulate autogenous tooth graft removed with organic matter and type I collagen addition on bone regeneration and to validate the possibility of useful allograft material for jaw defects. Material and methods Autogenous tooth bone maker (Korean Dental Solution® KOREA) made particulate autogenous tooth not including organic matter. We used to the developed tooth grafts for experiment. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Besides, APDDM exhibits good biocompatibility, owing to its structural components, which are composed of low‐crystalline hydroxyapatite (HA) and other calcium phosphate minerals, similar to human bone tissue 51 . The inorganic component of APDDM plays a critical role in space maintenance and osteoconduction, while the organic component supports cells and proteins for bone healing and promotes vascularization 52 . In addition, APDDM contains various growth factors, such as transforming growth factor β, bone morphogenetic protein (BMP), and vascular endothelial growth factor, 53 which induce osteoblastic differentiation of stem cells, promote the proliferation and migration of osteoblasts and osteocytes, and accelerate vessels formation, stimulating bone deposition by regulating gene expression 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, APDDM exhibits good biocompatibility, owing to its structural components, which are composed of low‐crystalline hydroxyapatite (HA) and other calcium phosphate minerals, similar to human bone tissue 51 . The inorganic component of APDDM plays a critical role in space maintenance and osteoconduction, while the organic component supports cells and proteins for bone healing and promotes vascularization 52 . In addition, APDDM contains various growth factors, such as transforming growth factor β, bone morphogenetic protein (BMP), and vascular endothelial growth factor, 53 which induce osteoblastic differentiation of stem cells, promote the proliferation and migration of osteoblasts and osteocytes, and accelerate vessels formation, stimulating bone deposition by regulating gene expression 54 .…”
Section: Discussionmentioning
confidence: 99%
“…51 The inorganic component of APDDM plays a critical role in space maintenance and osteoconduction, while the organic component supports cells and proteins for bone healing and promotes vascularization. 52 In addition, APDDM contains various growth factors, such as transforming growth factor β, bone morphogenetic protein (BMP), and vascular endothelial growth factor, 53 which induce osteoblastic differentiation of stem cells, promote the proliferation and migration of osteoblasts and osteocytes, and accelerate vessels formation, stimulating bone deposition by regulating gene expression. 54 The noncollagenous proteins present in DDM, such as dentin sialoproteins 51 and dentin phosphoproteins, are also involved in bone formation.…”
Section: Arp At Periodontally Compromised Sockets Using Apddmmentioning
confidence: 99%
“…This led to a time-dependent increase in BMD and TbTh in the particle groups. Bone grafting surgery for implant installation has been widely performed in patients with alveolar BV deficiency [ 37 ]. Popularly used with bone grafting material, rhBMP-2 successfully induces new bone regeneration in guided bone regeneration (GBR), maxillary sinus augmentation, and bone defects after cyst enucleation [ 23 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to its high extraction cost, the research on it has only achieved a simplified bionic structure ( Liao et al, 2021 ). Mingu K et al found that collagen played a role in bone formation in the repair of calvarial defects in rabbits ( Kim et al, 2021 ). Bio-Gide combined with Bio-Oss, a resorbable bone filler, can be used for bone regeneration and repair ( Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%